2016
DOI: 10.1080/02688697.2016.1226257
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous haematoma from vertebral artery arterio-venous fistula in a patient with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by a mutation on chromosome 17. Vascular abnormalities are recognised complications of NF1. These include aneurysms, stenoses, arteriovenous malformations, fistulae, etc. We report the case of a young gentleman with NF1 with a spontaneous cervical bleed from an arteriovenous fistula arising from the left vertebral artery, and illustrate the various management options and difficulties arising from rapid fistula formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There have been 4 cases of cervical subcutaneous hemorrhage due to an NF1-associated vertebral AVF, including the present case 2 , 7 , 11 ( Table 1 ). Of them, Narayanamurthy et al 7 reported a fatal case of cervical spontaneous hemorrhage that underwent endovascular obliteration followed by surgical hematoma removal to prevent airway obstruction.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…There have been 4 cases of cervical subcutaneous hemorrhage due to an NF1-associated vertebral AVF, including the present case 2 , 7 , 11 ( Table 1 ). Of them, Narayanamurthy et al 7 reported a fatal case of cervical spontaneous hemorrhage that underwent endovascular obliteration followed by surgical hematoma removal to prevent airway obstruction.…”
Section: Discussionmentioning
confidence: 80%
“…There have been 4 cases of cervical subcutaneous hemorrhage due to an NF1-associated vertebral AVF, including the present case 2 , 7 , 11 ( Table 1 ). Of them, Narayanamurthy et al 7 reported a fatal case of cervical spontaneous hemorrhage that underwent endovascular obliteration followed by surgical hematoma removal to prevent airway obstruction. However, uncontrollable bleeding from the vasculature and damaged tissue required wound packing and transfusion of red blood cells, fresh frozen plasma, and platelets, resulting in a fatal outcome.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Endovascular approaches are generally recommended as the initial treatment in most DAVFs, and open surgical techniques have high risk of bleeding due to the vascular fragility common in NF1. 7,8 Depending on the anatomy, a trans-arterial, transvenous, combined transarterial/transvenous approach can be used to cure a DAVF. 9 Multiple embolisation agents can be used.…”
Section: Discussionmentioning
confidence: 99%